Self resilience in terms of regional origin among students - Ririanti Rachmayanie J; Akhmad Sugianto; Fiya Hukmuti (Universitas Negeri Padang, 2022)
Students who come from various regions with their own culture need self-resilience to be able to adjust to the conditions in their new environment. Self-resilience is the ability of individuals to face difficulties or obstacles become natural to live. Every Guidance and Counseling student has self-resilience different; this can be seen from the way students deal with and react to problems in a new environment, one of which is shock culture. This study por to determine the self-resilience of guidance and counseling students in terms of their area of origin. This research uses a quantitative approach with comparative research types. The data collection instrument used was a questionnaire. with a random sampling technique that is taking a random sample from the existing population. Data analysis techniques using descriptive statistics and analysis test chi-square. The focus in this study is to determine the differences in self resilience in terms of regional origin. Based on the results of the data analysis test, it was found that 91% of self-resilience was distinguished by regional origin. Based on these results it can be concluded that there are differences in self-resilience in terms of regional origin in the guidance and counseling students.